Grain size distribution for sediment samples of Ludwig Prandtl cruise LP20200629 - Catharina Petrauskas; Madita Kruse; Ole Klein; Fadi Ragea El Gareb; Hans-Burkhard Erbslöh; Anna Ebeling; Daniel Pröfrock (PANGAEA, 2024)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in and around offshore wind farms of the German Bight between 22.07.2020 and 25.07.2020 within the context of the Hereon-BSH project OffChEm. The sediment samples were taken by a box grab and analyzed for their grain size distribution by laser diffraction.